The impact of MIS on the promotion of lean production in industrial companies - Al Taha, Abdul Hadi Hussein Mohammed; Al-Shalabi, Riyad (Journal of Economic, Administrative and Legal Sciences, 2017)
The aim of this study was to identify the "Impact of Management Information Systems on the promotion of lean production in industrial companies". To achieve the objective of the study, a questionnaire was developed and its validity and stability were verified. The study population consisted of all employees from the upper and middle administrative levels of industrial companies in Alhasan industrial city. The researcher took a random sample of 85 persons. The data were analyzed using the SPSS in order to reach the goals and objectives of this study. After analyzing the data, the study fulfills a set of results, the most important of which is that, there is an impact of the MIS on promoting the production of industrial enterprises. The study recommended the need to develop the skills of human resources in line with the requirements of the lean production, as well as the need to involve staff with specialized courses to raise their efficiency in terms of lean production.